SUPERVISI AKADEMIK SEBAGAI USAHA PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN DARING DI SDN KALIBANTENG KIDUL 02 SEMARANG - Azizah, Nur (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
Many teachers are not able to teach communicatively in learning, as happened in SDN Kalibanteng Kidul 02 Semarang City which on average is less able to teach well in online learning, teachers only give assignments to students without providing further explanation and good guidance ., from 10 teachers there are only 4 teachers who are able to carry out the online learning process using various media, not only by giving assignments to students. The lack of quality of teacher online learning during the pandemic is one of the problems that must be overcome by school principals by carrying out academic supervision. This study is intended to answer the following problems: 1 How is the implementation of academic supervision carried out by school principals to improve teacher performance in online learning at SDN Kalibanteng Kidul 02 Semarang City for the 2020/2021 academic year?. 2) Is there an increase in teacher performance in online learning after academic supervision is carried out at SDN Kalibanteng Kidul 02 Semarang City for the 2020/2021 academic year?. These problems are discussed through classroom action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation and reflection. The results showed that: 1) The implementation of academic supervision carried out by school principals to improve teacher performance in online learning at SDN Kalibanteng Kidul 02 Semarang City for the 2020/2021 academic year was carried out by providing direction and guidance to teachers to be able to utilize and apply web-based learning In the learning that is carried out, the teacher is also given the opportunity to practice the application under the guidance and direction of the researcher and followed by classroom observations to observe the teacher's way of doing online learning. 2) There was an increase in teacher performance in online learning after academic supervision was carried out at SDN Kalibanteng Kidul 02 Semarang City in the 2020/2021 school year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle where in the first cycle there were 19 teachers or 67.9 %, and in the second cycle there were 25 teachers or 89.3%. These results indicate that these results are in line with expectations.